Fostering an Inclusive Academic Workforce: Assessing the Impact of Age, Ethnic and Educational Diversity on Employee Performance - Padam Bahadur Lama; Prem Bahadur Budhathoki; Hari Prasad Ojha (Business Ethics and Leadership)
The performance of the workforce relies on organizational leaders who embrace strategic paths with diverse inclusion to foster performance in a globalized era. Thus, effective leadership roles contribute to properly managing diverse workforces in the organization, ultimately driving toward better performance. However, ambiguous evidence fostering the performance of personnel through inclusive diversity is yet to exist, manifesting distinct consequences. Linking to the existing theoretical gap, this research aims to discover the influence of workforce diversity comprising age, ethnicity, and educational diversity on employee performance by deriving evidence from the higher education sector in Kathmandu, Nepal. This research presents and investigates three research hypotheses: age diversity has a positive effect on employee performance, education diversity has a positive effect on employee performance, and ethnic diversity has a positive impact on employee performance. These formulated hypotheses and research questions were assessed by accumulating the primary data sources of faculty members working in the higher education sector in Kathmandu, Nepal. Thus, the research used a descriptive and explanatory research strategy within a deductive framework to evaluate the existing theory and test the generated hypothesis. Further, cross-sectional data were acquired from faculty members via a purposive sampling approach. A structured questionnaire was formed into two different segments for general background information and an opinion-based survey with five-point Likert scale items. It was distributed physically to 295 faculty members of the higher education sector in Kathmandu. The study utilized only 168 useful responses as some of the responses were incomplete. Descriptive and inferential statistical methods were used, including frequency, percentage, mean, and standard deviation for descriptive statistics, as well as correlation and regression analysis employed to evaluate associations and impacts among the variables. The findings of the research indicated a favorable and significant impact of age diversity on employee performance. Likewise, ethnic diversity favorably and significantly affected employee performance. Finally, the results showed the favorable and substantial effect of educational diversity on employee performance. The findings of this research can contribute to enhancing the current literature and create a benchmark for academic institutions, policymakers, and other key stakeholders to endorse informed decisions for promoting an inclusive workforce.